A COMPARATIVE STUDY ON ENDURANCE ABILITY AMONG BASKETBALL AND HANDBALL PLAYERS OF SRI VENKATESWARA UNIVERSITY - Babu, P.Madhusudhana (The journal of contemporary issues in business and government, 2007)
Aerobic Endurance is the amount of oxygen intake during exercise. Aerobic Endurance is the time which you can exercise, without producing lactic acid in your muscles.Aerobic means “with oxygen”, and refers to the use of oxygen in the body’s metabolic or energy – generating process.Basketball is a sport, generally played by two teams of five players on a rectangular court Handball also known as team handball, Olympic handball, European team handball, European handball, or Borden ball is a team sport in which two teams of seven players each (six outfield players and a goalkeeper) pass a ball to throw it into the goal of the other team.